The Books are Harder: Enhancing the Teaching of Reading Comprehension in The Senior Primary Classes - Keogh, Aoife Joy (STER, 2024)
This research describes the experiences of a final year BEd student undertaking school placement with a cohort of sixth class students in an urban non-disadvantaged Irish primary school with a class size of twenty eight students. The article provides an overview of an action research project (ARP) which focuses on enhancing the teaching of reading comprehension in the senior classes of primary school in order to enable students to overcome challenges.
Keywords: Literacy; Reading; Reading comprehension; Language learning; Pedagogy; Education--Ireland; Reading comprehension